2019
DOI: 10.1007/s00103-019-03019-4
|View full text |Cite
|
Sign up to set email alerts
|

Kohlenmonoxid – ein unterschätztes Risiko? Bekanntheit, Wahrnehmung, Wissen und Präventionsverhalten

Abstract: mitVergiftungen in Zusammenhang stehenden Diagnosen laut Einteilung der Internationalen statistischen Klassifikation der Krankheiten und verwandter Gesundheitsprobleme (ICD 10) der Weltgesundheitsorganisation (WHO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
(11 reference statements)
0
0
0
3
Order By: Relevance
“…[ 10 ] However, a study on awareness, perception and knowledge of CO poisoning has revealed that more than one-third of the interviewees believe that CO can be identified by its odour, smoke or the smoke alarm signal. [ 11 ] As such, this may convey a false sense of security, and the public should be educated on the differences between smoke and CO detectors. The cost of a CO detector is low (USD 15–60), and has a lifespan of 5–10 years with no maintenance cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] However, a study on awareness, perception and knowledge of CO poisoning has revealed that more than one-third of the interviewees believe that CO can be identified by its odour, smoke or the smoke alarm signal. [ 11 ] As such, this may convey a false sense of security, and the public should be educated on the differences between smoke and CO detectors. The cost of a CO detector is low (USD 15–60), and has a lifespan of 5–10 years with no maintenance cost.…”
Section: Discussionmentioning
confidence: 99%
“…As most CO exposures are accidental, increased public awareness and CO detectors will help prevent and reduce the incidence. [ 11 ] Local studies should also be performed to look at the risk of CO exposure in Singapore to assist authorities in considering the mandate of CO detectors in high-risk areas to reduce the risk of accidental CO poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Holzpelletheizungen kann es in den Pellet-Lagerstätten durch natürliche Abbauprozesse von Fettsäuren im Holz zur Bildung von hohen Konzentrationen an Kohlenmonoxid kommen [18,19]. Diese Tatsache ist auch vielen Besitzern von Holzpellet-Heizungen unbekannt [20].…”
Section: Quellen Für Kohlenmonoxid In Der Innenraumluftunclassified
“…In einer Untersuchung konnten mehr als 90 % der Befragten Brände in Gebäuden, den laufenden Motor in der Garage oder den defekten Ofen/Kaminabzug als Gefahrenquelle benennen. Dagegen waren Shisha-Rauchen und die Lagerung von Holzpellets in geschlossenen Räumen als Ursache deutlich weniger bekannt [4].…”
Section: Introductionunclassified
“…Durch gesetzliche Regelungen sind Rauchmelder in Wohngebäuden in Deutschland inzwischen weit verbreitet, aber nur 15 % der Befragten gaben an, ein CO-Warngerät zu besitzen [4]. In der Befragung zeigte sich auch ein weitverbreiteter Irrtum über die technischen Möglichkeiten von Rauchmeldern.…”
Section: Introductionunclassified